Matching pH values for antibody stabilization and crystallization suggest rationale for accelerated development of biotherapeutic drugs. Issue 3 (23rd November 2019) - Sjuts, Hanno; Schreuder, Herman; Engel, Christian K.; Bussemer, Till; Gokarn, Yatin
Abstract: Monoclonal antibodies (mAbs) are currently leading products in the global biopharmaceutical market. Multiple mAbs are in clinical development and novel biotherapeutic protein scaffolds, based on the canonical immunoglobulin G (IgG) fold, are emerging as treatment options for various medical conditions. However, fast approvals for biotherapeutics are challenging to achieve, because of difficult scientific development procedures and complex regulatory processes. Selecting molecular entities with superior physicochemical properties that proceed into clinical trials and the identification of stable formulations are crucial developability aspects. It is widely accepted that the solution pH has critical influences on both the protein's colloidal stability and its crystallization behavior. Furthermore, proteins usually crystallize best at solution conditions that enable high protein solubility, purity, stability, and monodispersity. Therefore, we hypothesize that the solution pH value is a central parameter that is linking together protein formulation, protein crystallization, and thermal protein stability. In order to experimentally test this hypothesis, we have investigated the effect of the solution pH on the thermal stabilities and crystallizabilities for three different mAbs. Combining biophysical measurements with high throughput protein (HTP) crystallization trials we observed a correlation in the buffer pH values for eminent mAb stability and successful crystallization. Specifically, differential scanning fluorimetry (DSF) was used to determine pH values that exert highest thermal mAb stabilities and additionally led to the identification of unfolding temperatures of individual mAb domains. Independently performed crystallization trials with the same mAbs resulted in their successful crystallization at pH values that displayed highest thermal stabilities. In summary, the presented results suggest a strategy how protein crystallization could be used as a screening method for the development of biotherapeutic protein formulations with improved in vitro stabilities.